Laboratory simulations of fluid/gas induced micro-earthquakes: application to volcano seismology - Benson, Philip M.; Vinciguerra, Sergio; Nasseri, Mohamed H. B.; Young, R. Paul (Frontiers in Earth Science, 2014)
Understanding different seismic signals recorded in active volcanic regions allows geoscientists to derive insight into the processes that generate them. A key type is known as Low Frequency or Long Period (LP) event, generally understood to be generated by different fluid types resonating in cracks and faults. The physical mechanisms of these signals have been linked to either resonance/turbulence within fluids, or as a result of fluids “sloshing” due to a mixture of gas and fluid being present in the system. Less well understood, however, is the effect of the fluid type (phase) on the measured signal. To explore this, we designed an experiment in which we generated a precisely controlled liquid to gas transition in a closed system by inducing rapid decompression of fluid-filled fault zones in a sample of basalt from Mt. Etna Volcano, Italy. We find that fluid phase transition is accompanied by a marked frequency shift in the accompanying microseismic dataset that can be compared to volcano seismic data. Moreover, our induced seismic activity occurs at pressure conditions equivalent to hydrostatic depths of 200–750 m. This is consistent with recently measured dominant frequencies of LP events and with numerous models.